2021
DOI: 10.1002/ajb2.1607
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary divergence of potential drought adaptations between two subspecies of an annual plant: Are trait combinations facilitated, independent, or constrained?

Abstract: Premise Whether drought‐adaptation mechanisms tend to evolve together, evolve independently, or evolve constrained by genetic architecture is incompletely resolved, particularly for water‐relations traits besides gas exchange. We addressed this issue in two subspecies of Clarkia xantiana (Onagraceae), California winter annuals that separated approximately 65,000 years ago and are adapted, partly by differences in flowering time, to native ranges differing in precipitation. Methods In these subspecies and in re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 117 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…Though these scenarios are possible, the population's large demographic decline during the drought suggests a severe environmental perturbation similar to that at S22, and any "pre" adaptation, if present, was not sufficient to avoid large demographic consequences. It is also possible that advanced phenology simply did not confer fitness benefits during drought at KYE, though this would be contrary to both general trends in plants [40] and the well documented relationship between early flowering time and adaptation to aridity in C. x. xantiana and close relatives [37,41,[57][58][59][60].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Though these scenarios are possible, the population's large demographic decline during the drought suggests a severe environmental perturbation similar to that at S22, and any "pre" adaptation, if present, was not sufficient to avoid large demographic consequences. It is also possible that advanced phenology simply did not confer fitness benefits during drought at KYE, though this would be contrary to both general trends in plants [40] and the well documented relationship between early flowering time and adaptation to aridity in C. x. xantiana and close relatives [37,41,[57][58][59][60].…”
Section: Discussionmentioning
confidence: 97%
“…However, gene flow is unlikely to be strong enough over this short time window to prevent evolutionary change, especially given that our populations are isolated from others (>1 kilometer) and lack adaptations for long-distance dispersal. It is also possible that advanced phenology simply did not confer fitness benefits during drought at KYE, though this would be contrary to both general trends in plants [44] and the well-documented relationship between early flowering time and adaptation to aridity in C. xantiana and close relatives [37,45,61,6870]. It is also interesting that, in contrast to expectations, empirical and simulation results suggested that phenotypic optima did not return to their pre-drought level after the drought ended.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown evolution of drought avoidance rather than escape or evolutionary shifts to later flowering following drought (Anstett et al, 2021 ) or a lack of evolutionary response to drought (Vtipil & Sheth, 2020 ). Which strategy is favored is likely to depend on the environmental conditions and pattern of drought, as well as on the characteristics of the organism (Burnette & Eckhart, 2021 ; Kooyers et al, 2021 ). Interestingly, earlier flowering was favored in our study despite the fact that drought was implemented mostly throughout the study, rather than in a pattern of decreasing moisture availability, although the plants may have experienced increasing negative effects of the drought over the course of the growing season, and did experience saturating conditions early in the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the progressive loss of soil moisture that characterizes late spring in Mediterranean climates, plant species that are adapted to such conditions offer an opportunity to identify the traits that evolve in response to the risk of dehydration. Recent studies of conspecific and interspecific populations exposed to such risk have tested predictions concerning the phenotypes that will evolve when soil moisture is low, revealing the potential for the rapid evolution of traits that promote drought escape (e.g., relative fast germination and growth, earlier flowering, and larger leaf size) (Bazzaz, 1979;Heschel and Riginos, 2005;Franks et al, 2007;Lowry et al, 2008;Wu et al, 2010;Franks, 2011;Kigel et al, 2011;Heschel et al, 2017;Dickman et al, 2019;Metz et al, 2020) or dehydration avoidance (e.g., slower growth, higher water-use efficiency, decreased transpiration, greater succulence, higher trichome density, and smaller leaf size) (Arntz and Delph, 2001;Kooyers et al, 2015;Heschel et al, 2017;Anstett et al, 2021;Burnette and Eckhart, 2021). Studies of the genus Mimulus have provided particularly clear cases in which differences between populations or higher taxa in their exposure to drought are associated with phenotypic divergence in flowering time, with early flowering associated with more arid conditions (Lowry et al, 2008(Lowry et al, , 2009Kigel et al, 2011;Ivey and Carr, 2012;Wolfe and Tonsor, 2014;Kooyers et al, 2015;Metz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%